The clinical relevance of surgical specimens for RNA sequencing in lung cancer: a cohort study - Eom, Jung Seop; Kim, Soo Han; Kim, Kyungbin; Kim, Ahrong; Ahn, Hyo Yeong; Mok, Jeongha; Cho, Jeong Su; Lee, Min Ki; Song, Ju Sun; Kim, Mi-Hyun (Frontiers in Oncology, 2024)
BackgroundMolecular screening using next-generation sequencing (NGS) in the pathologic evaluation of lung cancer is considered the standard in clinical practice; hence, we evaluated the diagnostic yields of various sampling methods for NGS.MethodsNGS data from patients with lung cancer at the Pusan National University Hospital (Busan, South Korea), admitted October, 2020–April, 2023, was obtained. The sampling methods by which NGS data was obtained were divided into surgical and nonsurgical. Surgical methods included thoracoscopic surgery, surgical biopsy from the metastatic site, and lymph node excisional biopsy, whereas nonsurgical methods included bronchoscopy procedures and medical thoracoscopic biopsy.ResultsIn total, we obtained 319 patients’ NGS data:150 (47.0%) and 169 (53.0%) was obtained using surgical and nonsurgical methods, respectively. The overall diagnostic yield of NGS analysis was 97.5% for all samples. There were no significant differences in the success rates of deoxyribonucleic acid sequencing between surgical and nonsurgical sampling methods (98.0% vs. 96.4%, p = 0.313). On the other hand, the success rate of ribonucleic acid (RNA) sequencing was significantly lower in the surgical method group (78.0% vs. 92.3%; p < 0.001). Multivariate analysis showed that surgical sampling significantly correlated with RNA sequencing failure (Odd Ratio 4.128, 95% Confidence Interval 1.681–10.133, p = 0.002).ConclusionsSmall samples obtained using nonsurgical procedures are suitable for NGS analysis in clinical practice. However, surgical sampling showed a relatively lower success rate for RNA sequencing than nonsurgical sampling. This information may help in the development of protocols to reduce RNA degradation during the surgical process.